Chinese herbal medicine promotes growth by improving nutrient utilization and rumen microbiota in suckling lambs - Wang, Yan; Wu, Yinglian; Qin, Rongyan; Chen, Xiangyu; Liu, Limeng; Wang, Lele; Wang, Wenqi; Liu, Yanfeng (Frontiers in Microbiology, 2025)
This study investigated the effects of compound Chinese herbal medicine (CCHM) on nutrient digestibility, rumen fermentation parameters, and microbial structure in suckling lambs. Sixty Lambs born as twins (from the same ewe), each 8 days old, were randomly assigned to two groups. The control and treatment groups received 0 and 0.2% CCHM in the basal diet, respectively. Digestion experiments were conducted during the trial. Rumen fluid samples were collected from slaughtered lambs in the final week for microbiome analysis. The results indicated that average daily gain and average daily feed intake were significantly improved by CCHM. The apparent digestibility of dry matter and acid detergent fiber also increased significantly. CCHM supplementation elevated Ammonia nitrogen (NH3-N), total volatile fatty acids (TVFAs), acetate, and propionate concentrations in the rumen. The relative abundance of Firmicutes, Actinobacteria, Patescibacteria, Succiniclasticum, Selenomonas, Olsenella, and Shuttleworthia increased in the treatment group. Linear discriminant analysis Effect Size (LEfSe) revealed ten bacterial groups significantly enriched in the treatment group. These included Patescibacteria (Phylum), Negativicutes and Saccharimonadia (Class), Saccharimonadia and Rhodobacterales (Order), Saccharimonadiahe and Rhodobacteraceae (Family), and Prevotell-9, Saccharimonadales, and Limosilicobacillus (Genus). Thirteen CAZyme families were detected. Two enzyme families, GH34-5 and CBM4, were enriched in the control group, while eleven families were enriched in the treatment group: GT14, GH89, GH84, GH63, GH5-36, CBM58, PL37, GH85, GH165, GH110, and GH50. Correlation analysis between rumen bacteria, carbohydrate enzymes, and fermentation parameters showed a positive correlation between Saccharimonadales and GH63. Limosilactobacillus showed a positive correlation with CBM58. Negative correlations were found between Romboutsia and both GT14 and PL37. GH84, GH165, GH85, and GH50 were positively correlated with NH3-N concentration. CBM58, GT14, GH89, GH110, GH50, and PL37 showed positive associations with TVFAs. This study demonstrates that dietary supplementation with CCHM during the suckling period improves growth performance, enhances nutrient digestibility, increases rumen fermentation capacity, modulates microbial abundance, and promotes lamb development in Hu sheep.